Focus Licensing at the Left Periphery in Japanese Right Dislocation. (23rd January 2019) - Abe, Jun
Abstract: In this paper, I argue that there is a designated focus position in the CP layer in Japanese and that this position is activated only in limited contexts, such as ellipsis contexts. I argue that in fact one of the best cases for such a designated focus position involves Japanese right dislocation. Assuming the biclausal analysis of this construction, which involves ellipsis, I argue that the postverbal phrase occupies the position in the CP layer designated for a focused phrase. Finally, addressing the question of whether Focus projections can be activated only in root clauses, I investigate what may be called massively pied‐piped cases of Japanese sluicing and demonstrate that Focus projections can be activated by the same types of embedded clauses as Topic projections.